Mitochondrial Energy-Regulating Effect of Atractyloside Inhibits Hepatocellular Steatosis Through the Activation of Autophagy - Zhang, Pengfei; Li, Lijun; Sun, Huimin; Zhang, Yipeng; Zhang, Guoliang; Zhang, Tianyu; Zeng, Changchun (Frontiers in Pharmacology, 2020)
Background and Aim: Atractyloside (ATR), a mitochondrial uncoupler, is known for its specific inhibition of mitochondrial oxidative phosphorylation. Previous studies have reported that moderate mitochondrial uncoupling effect is beneficial to increase the decomposition and clearance of hepatic lipid, prevent the occurrence of fatty liver diseases. Moreover, the beneficial effects of mitochondrial uncouplers on type 2 diabetes and metabolic syndromes have been consistently observed. The present study investigated the effect of ATR on steatosis level of HepG2 cells treated with free fatty acid (FFA). Methods: Intracellular triglyceride level and Oil Red O staining were assessed, the mitochondrial adaptation and ADP/ATP ratio were analysed, the protein level of AMPK, mTOR and LC3B, autophagic flux, and the co-localization of LC3B with lipid droplets was performed. Results: ATR treatment inhibited the activity of mitochondrial respiratory chain complexes I and IV, decreased the mitochondrial membrane potential, and increased the ADP/ATP ratio in the FFA-treated cells. Furthermore, ATR increased the gene expression and protein level of LC3B and promoted the autophagic flux processing from early autophagosome to late autolysosome by increasing the protein level of AMPKα and decreasing the protein level of mTOR. An increased number of autophagosomes (LC3B) was also observed in the lipid droplets. ATR treatment accelerated lipid degradation in the FFA-treated cells, and the lowest lipid content was observed in the cell group with 7.5 μM ATR. Conclusion: Low concentrations (2.5, 5, and 7.5 μM) of ATR treatment could activate autophagy to accelerate the degradation of TGs in steatosis HepG2 cells; the mechanism may be related to the activation of the AMPK/mTOR pathway induced by the increased ADP/ATP ratio. In addition, the ideal concentration of ATR for improving steatotic HepG2 cells was 7.5 μM.